1999
DOI: 10.1085/jgp.114.2.167
|View full text |Cite
|
Sign up to set email alerts
|

Movement of Voltage Sensor S4 in Domain 4 Is Tightly Coupled to Sodium Channel Fast Inactivation and Gating Charge Immobilization

Abstract: The highly charged transmembrane segments in each of the four homologous domains (S4D1–S4D4) represent the principal voltage sensors for sodium channel gating. Hitherto, the existence of a functional specialization of the four voltage sensors with regard to the control of the different gating modes, i.e., activation, deactivation, and inactivation, is problematic, most likely due to a functional coupling between the different domains. However, recent experimental data indicate that the voltage sensor in domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
98
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(105 citation statements)
references
References 49 publications
6
98
0
1
Order By: Relevance
“…6A). The first step initiates fast inactivation and corresponds to the transition of VSDIV from the resting state to the activated state, a step that accounts for the majority of gating charge movement (15,(32)(33)(34)(35). The second, more weakly voltage-dependent, transition moves the activated VSDIV to an immobilized state that is coupled to selectivity filter collapse and slow inactivation, as has been proposed for other voltage-gated channels (14,17,36).…”
Section: Resultsmentioning
confidence: 79%
“…6A). The first step initiates fast inactivation and corresponds to the transition of VSDIV from the resting state to the activated state, a step that accounts for the majority of gating charge movement (15,(32)(33)(34)(35). The second, more weakly voltage-dependent, transition moves the activated VSDIV to an immobilized state that is coupled to selectivity filter collapse and slow inactivation, as has been proposed for other voltage-gated channels (14,17,36).…”
Section: Resultsmentioning
confidence: 79%
“…Although there are fewer studies on the discrete transitions in the activation processes of Na channels, the S4's from domains I, II, and III are thought to be principally involved in channel activation (2) while inactivation has been associated with the S4 in DIV (8,10,11,21,22,37,43,44). Studies of individual florescent-tagged voltage sensors in rat skeletal muscle Na channels (rSkM1, Na V 1.4) showed that the S4's in domains I-III all translocated rapidly during a step depolarization consistent with their role in the activation process (10).…”
Section: Discussionmentioning
confidence: 99%
“…I Na decay in WT channels is critically dependent upon inactivation from the open state (8,11,14,21,22,37,43,44); consequently the more rapid decay of I Na following stabilization of the DII-S4 suggests that inactivation has also become faster. Furthermore, the large negative shift in the V ½ of the steady-state Na channel availability curve after DII-S4 was stabilized also suggests it has a role in closed state inactivation, presumably by helping form or helping control Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, although sodium channels are constructed of four homologous domains (DI-DIV), each domain does not contribute identically to channel gating (Hille, 2001). In addition, inactivation and activation are coupled because channel inactivation preferentially immobilizes the DIII-and DIV-associated activation gating movements (Cha et al, 1999;Kuhn and Greeff, 1999). Additional discrepancies between HH-predicted and experimentally observed sodium channel behavior have also been described including gating currents, current fluctuation analysis, singlechannel activity, and activation kinetics (Patlak, 1991;Hille, 2001; Baranauskas and Martina, 2006;Naundorf et al, 2006).…”
Section: Introductionmentioning
confidence: 99%